Method for preparing cementing material and roadbed building material through autoclaved activation of waste incineration fly ash

Through the autoclave process, waste incineration fly ash is activated, and mineral phase materials with gelling characteristics are prepared, which solves the problems of high costs and environmental pollution in the existing technology, and realizes the effective resource utilization of fly ash and the efficient preparation of roadbed building materials.

CN119874226APending Publication Date: 2025-04-25SHANGHAI PUDONG XINQU XINGSHENG ROADBED MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510059287.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing waste incineration fly ash treatment technology has problems such as high cost, environmental pollution and low resource utilization efficiency, especially when the high-temperature melting technology has high energy consumption and high risk of secondary pollution.

Method used

The waste incineration fly ash is activated by the autoclave process, and the calcium-silicon-aluminum system mineral phase precursor with gelling characteristics is prepared by reaction with auxiliary materials and additives, and the mineral phase precursor with gelling characteristics is generated through water washing and detoxification and high temperature activation to generate materials with good gelling properties. This material can be used to prepare roadbed building materials.

Benefits of technology

The effective removal of heavy metals and chloride salts in fly ash is achieved, the risk of secondary pollution is reduced, and the process is simple and the cost is low. The product has good gelling performance and detoxification effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242373620000041
    Figure BDA0005242373620000041
  • Figure BDA0005242373620000042
    Figure BDA0005242373620000042
  • Figure BDA0005242373620000051
    Figure BDA0005242373620000051
Patent Text Reader

Abstract

The invention relates to a method for preparing a cementing material through autoclaved activation of waste incineration fly ash and a method for preparing a roadbed building material by using the cementing material, and belongs to the technical field of resource utilization of household garbage. The preparation method of the cementing material comprises the following steps: stirring 50-80% by mass of fly ash, 18-50% by mass of an auxiliary material, 0-2% by mass of an additive and water accounting for 10-30% of the total mass of a solid material, and pressing for 4-5 minutes at the high pressure of 10-30 MPa for molding; placing the molded test block in an autoclave, and carrying out autoclave reaction at 150-250 DEG C for 1-5 hours under the pressure of 0.5-1.2 MPa; and crushing the autoclaved test block, rinsing the crushed test block with water for 1-3 times, and activating the rinsed test block in a high-temperature furnace at 600-900 DEG C for 20-60 minutes. The material with the gelling characteristic is prepared through the method of preparing the gelling mineral phase precursor through steaming, detoxifying through water washing and activating and exciting the gelling characteristic of the material at high temperature, and the method has the advantages of being simple in process, low in cost and good in product detoxification effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a treatment process for degrading toxic fly ash from garbage incineration, in particular to a method for preparing a gelling material by using an autoclave process, and a method for preparing roadbed building materials by using the gelling material, belonging to the technical field of resource utilization of domestic garbage. Background Art

[0002] The incineration energy conversion of solid waste is one of the most widely used treatment methods for volume reduction, harmlessness and energy resource utilization. The captured materials produced by the flue gas purification system and the bottom ash settled at the bottom of the flue and chimney during the incineration of solid waste are collectively referred to as incineration fly ash. According to the "National List of Hazardous Wastes (2021 Edition)", fly ash produced by the incineration of domestic waste is classified as hazardous waste (HW18).

[0003] At present, domestic waste incineration fly ash treatment and disposal technologies mainly include high-temperature sintering technology, high-temperature melting technology, low-temperature pyrolysis-water washing and detoxification technology, water washing and detoxification-high-salt wastewater discharge into the sea technology, and water washing-cement kiln coordinated disposal technology.

[0004] However, although the secondary fly ash produced by high-temperature sintering disposal of fly ash contains a large amount of heavy metals, its quality still does not reach the level of smelting original ore, and since most heavy metals exist in the form of low-boiling point chloride salts, the feasibility of melting and recovering metals is low. At present, secondary fly ash is mainly treated by acid leaching extraction, chemical precipitation, multi-effect evaporation and salt separation, etc., which produces a large amount of wastewater and is easy to cause secondary pollution. There are still many problems to be solved in the application of high-temperature melting technology, such as high energy consumption of high-temperature melting, low thermal efficiency, high operating cost, oxidation loss of graphite electrodes by oxygen released by oxides in fly ash during the melting process, corrosion of refractory materials of melting furnace by chlorine rich in fly ash, control of soluble chlorine in molten glass, stability control of heavy metals in molten glass, large-scale disposal of molten glass, etc., all of which restrict the large-scale promotion and application of high-temperature melting technology of waste incineration fly ash. After low-temperature pyrolysis and detoxification, the fly ash is washed and removed through a multi-stage water washing process to remove a large amount of soluble heavy metals and chloride salts in the fly ash. However, the low-temperature pyrolysis process has high requirements for oxygen content, the air tightness of the continuous pyrolysis furnace is difficult to control, the output of the batch pyrolysis furnace is difficult to increase and the energy consumption is too high. The effect of large-scale treatment needs further verification. Although the water washing detoxification-high-salt wastewater discharge to the sea technology has a low disposal cost, a large amount of salt-containing wastewater can be treated by discharging it into the sea to significantly reduce operating costs. However, there are many restrictions on the discharge of salt-containing wastewater into the sea at the policy level, and its safety needs to be demonstrated through rigorous scientific analysis. In the cement kiln coordinated disposal process, due to the requirements of cement kilns on the chlorine content of the feed, a large amount of ash washing wastewater is generated in the fly ash pretreatment process that needs to be treated.

[0005] Therefore, there is an urgent need in this field to develop a waste incineration fly ash resource processing technology with lower cost and more environmentally friendly. Summary of the invention

[0006] In response to at least one of the above-mentioned problems existing in the prior art, the present application proposes a method for preparing a gelling mineral phase precursor by steam pressing, detoxifying by water washing, and stimulating the gelling properties of the material by high-temperature activation to prepare a material with gelling properties, and further using the gelling material to prepare roadbed building materials. The method has the characteristics of simple process, low cost, and good product detoxification effect.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a cementitious material by autoclaving and activating fly ash from waste incineration, comprising the following steps:

[0009] In terms of mass percentage, 50-80% fly ash, 18-50% auxiliary materials, 0-2% additives and water in an amount of 10%-30% of the total mass of the solid material are stirred, and pressed under a high pressure of 10-30 MPa for 4-5 minutes to form;

[0010] The formed test block is placed in an autoclave and reacted at 150-250°C for 1-5 hours at a pressure of 0.5MPa-1.2MPa;

[0011] After the autoclaved test block is crushed, rinsed with water 1-3 times, and placed in a high-temperature kiln for activation at 600-900℃ for 20-60min;

[0012] The product after activation is a gelling material, which can be crushed and ground for later use.

[0013] Preferably, the auxiliary material is a material containing silicon and aluminum components, including but not limited to natural minerals / ores, soil, various industrial solid byproducts / solid wastes, such as aluminum ash, fly ash, etc. In the auxiliary material, there is no strict requirement for the mass ratio of silicon to aluminum, and it is only required that the mass of silicon is higher than that of aluminum, which helps to preferentially generate a mineral phase dominated by silicates during the water washing process, and simultaneously form aluminosilicates and aluminates, thereby optimizing the mineral conversion process, improving the stabilization effect on harmful components in fly ash, and facilitating resource utilization.

[0014] Preferably, the additive is a reaction promoting activator, including but not limited to alkali, calcium salt, iron salt, aluminum salt, etc., such as lime.

[0015] In a second aspect, the present invention provides a method for preparing roadbed building materials using the above-obtained cementitious material, comprising the following steps:

[0016] According to the mass percentage, 70-90% of the gelling material, 0-10% of the active stimulating material, 5-10% of the dehydrating agent, and 5-10% of the additive are mixed with 15-40% of the solid mass of water, stirred, rolled and mixed, and then slurry is adjusted and molded to prepare a semi-finished roadbed brick, or after being formed by high pressure of 5-20MPa, it is placed in an autoclave at 140-220°C and autoclaved for 2-6 hours to prepare a semi-finished autoclaved brick; the semi-finished roadbed brick or the semi-finished autoclaved brick is cured for 1-10 days under the conditions of 0-40°C and relative humidity of 70-100% to obtain a finished roadbed brick or a finished autoclaved brick.

[0017] Preferably, the active stimulating materials are mainly silicon-containing or aluminum-containing materials, including but not limited to fly ash, silicon oxide, aluminum slag, bauxite, quartz sand, cement, etc. The purpose of adding the active stimulating materials is that when preparing the finished roadbed building materials, these materials hydrate to produce gelling properties faster, providing early strength of the roadbed materials.

[0018] Preferably, the dehydrating agent is lime, etc. The main function of the dehydrating agent is to absorb / lock free water when adding water to mix and make slurry, usually by using the water-absorbing property of lime to accelerate the drying speed of the slurry and advance the initial setting time.

[0019] Preferably, the additive is gypsum, etc. The addition of the gypsum additive helps to produce a synergistic effect with other components, increases the viscosity of the mixture after slurrying, and also helps to improve the early strength of the newly formed roadbed material.

[0020] This application has the following beneficial effects:

[0021] By adopting the above method, the calcium in the fly ash undergoes chemical reactions such as bond breaking and recombination with the silicon-aluminum materials in the auxiliary materials under the action of high temperature and high pressure water vapor during the autoclaving process, which prompts calcium oxide, silicon oxide, aluminum oxide and other less active oxides to generate calcium-silicon-aluminum system mineral phase precursors with gelling properties. After the autoclaved test blocks are crushed and rinsed, pollutants such as soluble heavy metals and chloride salts are transferred from the solid phase to the liquid phase through the diffusion and dissolution effect and fully removed. In the high-temperature activation process, the calcium-silicon-aluminum system mineral phase precursors with gelling properties generate calcium-silicon-aluminum mineral phase materials with strong gelling properties through reactions such as removal of bound water, condensation, and mineral phase bond breaking and recombination. At the same time, in the process of high-temperature activation of the material's gelling properties, organic pollutants such as dioxins in the fly ash are thermally decomposed and removed at high temperatures. DETAILED DESCRIPTION

[0022] The following examples and comparative examples are used to further describe the specific embodiments of the present invention. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0023] Example 1

[0024] A method for preparing a gelling material by autoclaving and activating fly ash from garbage incineration, comprising the following steps:

[0025] In terms of mass percentage, 50% fly ash, 50% fly ash (SiO2 is 58%, Al2O3 is 31%, and the others are 11%) and 15% water by solid mass are stirred and mixed, and then pressed at 10 MPa for 5 minutes to obtain a molded test block.

[0026] The molded test blocks were autoclaved in an autoclave at 160°C and 1.2 MPa for 3 hours, and after cooling, the test blocks were broken into 1-5 mm and rinsed with water for desalination. The solid product after rinsing was activated at 600°C in a rotary kiln for 60 minutes to obtain a gelled material.

[0027] The heavy metal leaching (HJ577), dioxin content, and soluble chlorine content of the cementitious material meet the requirements of the relevant standard HJ1134, and the cementitious performance meets the relevant requirements of the strength activity index in the standard GB / T 1596, as shown in Table 1.

[0028] Table 1 Pollutant indexes of cementitious materials

[0029]

[0030] Furthermore, the above-mentioned cementitious material is used to prepare roadbed building materials, and the preparation method includes the following steps:

[0031] According to the percentage by mass, 80% cementitious material, 10% fly ash (SiO2 is 58%, A12O3 is 31%, and the others are 11%), 5% lime, and 5% gypsum are mixed with 40% water of solid mass for slurry mixing and injection molding to prepare semi-finished roadbed bricks. After curing for 7 days at about 10°C and 70% humidity, the finished roadbed bricks are obtained.

[0032] The 7-day compressive strength of the finished roadbed brick is 18.5MPa, the 14-day compressive strength is 22.1MPa, and the 28-day compressive strength is 24.1MPa. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 2.

[0033] Table 2 Product contamination index test results

[0034]

[0035] Example 2

[0036] A method for preparing a gelling material by autoclaving and activating fly ash from garbage incineration, comprising the following steps:

[0037] In terms of mass percentage, 60% fly ash, 38% fly ash (SiO2 is 58%, A12O3 is 31%, and other 11%), 2% lime and 10% water by solid mass are stirred and mixed, and then pressed at 15 MPa for 4 minutes to obtain a molded test block.

[0038] The formed test block was autoclaved in an autoclave at 150°C and 0.5 MPa for 2 hours, and after cooling, the test block was broken into 1-5 mm and rinsed with water for desalination. The rinsed product was activated at 700°C in a rotary kiln for 40 minutes to obtain a gelled material.

[0039] The heavy metal leaching (HJ 577-2010), dioxin content, and soluble chlorine content of the cementitious material meet the relevant requirements of the HJ 1134-2020 standard, and the cementitious performance meets the relevant requirements of the strength activity index in GB / T 1596, as shown in Table 3.

[0040] Table 3 Contaminant indexes of cementitious materials

[0041]

[0042] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0043] According to the percentage by mass, 85% of cementitious material, 5% of silica powder, 5% of lime and 5% of gypsum are formed by high pressure at 20MPa and then autoclaved in an autoclave at 140°C for 6 hours to prepare an autoclaved brick semi-finished product. The autoclaved brick semi-finished product is cured for 5 days at 15°C and 100% humidity to obtain an autoclaved brick finished product.

[0044] The compressive strength of the finished autoclaved brick is 17.8MPa after 7 days, 28.6MPa after 14 days, and 32.7MPa after 28 days. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 4.

[0045] Table 4 Example 2 Product Contamination Index Detection Results

[0046]

[0047] Example 3

[0048] A method for preparing a gelling material by autoclaving and activating fly ash from garbage incineration, comprising the following steps:

[0049] In terms of mass percentage, 80% fly ash, 18% fly ash (SiO2 is 58%, A12O3 is 31%, and other 11%), 2% lime and 30% water by solid mass are stirred and mixed, and then pressed at 30 MPa for 4 minutes to obtain a molded test block.

[0050] The formed test block was autoclaved in an autoclave at 220°C and 0.8 MPa for 4 hours, and after cooling, the test block was broken into 1-5 mm and rinsed and desalted with water. The rinsed product was activated at 900°C in a rotary kiln for 20 minutes to obtain a gelled material.

[0051] The heavy metal leaching (HJ 577-2010), dioxin content and soluble chlorine content of the cementitious material meet the relevant requirements of the HJ 1134-2020 standard, and the cementitious performance meets the relevant requirements of the strength activity index in the GB / T 1596 standard.

[0052] Table 5 Pollutant indexes of cementitious materials

[0053]

[0054] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0055] According to the percentage by mass, 80% cementitious material, 10% fly ash (SiO2 is 58%, Al2O3 is 31%, and the others are 11%), 5% lime, and 5% gypsum are mixed with 30% water by solid mass for slurry mixing and injection molding to prepare semi-finished roadbed bricks. After curing for 10 days at about 0°C and 80% humidity, the finished roadbed bricks are obtained.

[0056] The 7-day compressive strength of the finished roadbed brick is 17.8MPa, the 14-day compressive strength is 25.8MPa, and the 28-day compressive strength is 29.6MPa. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 6.

[0057] Table 6 Product contamination index test results

[0058]

[0059] Example 4

[0060] A method for preparing a gelling material by autoclaving and activating fly ash from garbage incineration, comprising the following steps:

[0061] In terms of mass percentage, 70% fly ash, 30% fly ash (SiO2 is 58%, Al2O3 is 31%, and other 11%) and 25% water by solid mass are stirred and mixed, and then pressed at 22 MPa for 4 minutes to obtain a molded test block.

[0062] The formed test block was autoclaved in an autoclave at 250°C and 1.1 MPa for 5 hours, and after cooling, the test block was broken into 1-5 mm and rinsed and desalted with water. The rinsed product was activated at 800°C in a rotary kiln for 30 minutes to obtain a gelled material.

[0063] The heavy metal leaching (HJ 577-2010), dioxin content, and soluble chlorine content of the cementitious material meet the relevant requirements of the HJ 1134-2020 standard, and the cementitious performance meets the relevant requirements of the strength activity index in GB / T 1596, as shown in Table 7.

[0064] Table 7 Contaminant indexes of cementitious materials

[0065]

[0066]

[0067] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0068] According to the percentage by mass, 90% of cementitious material, 5% of lime and 5% of gypsum are formed by high pressure at 5MPa and then autoclaved in an autoclave at 220°C for 2 hours to prepare an autoclaved brick semi-finished product. After curing for 7 days at about 25°C and 90% humidity, the autoclaved brick finished product is obtained.

[0069] The compressive strength of the finished autoclaved brick is 15.9MPa after 7 days, 23.7MPa after 14 days, and 30.2MPa after 28 days. The heavy metal leaching test was carried out according to standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 8.

[0070] Table 8 Product contamination index test results

[0071]

[0072] Example 5

[0073] A method for preparing a gelling material by autoclaving and activating fly ash from garbage incineration, comprising the following steps:

[0074] In terms of mass percentage, 75% fly ash, 25% fly ash (SiO2 is 58%, Al2O3 is 31%, and the others are 11%) and 22% of water by solid mass are stirred and mixed, and then pressed at 18 MPa for 4 minutes to obtain a molded test block.

[0075] The formed test block was autoclaved in an autoclave at 190°C and 1.0 MPa for 1 hour, and after cooling, the test block was broken into 1-5 mm and rinsed with water for desalination. The rinsed product was activated at 750°C in a rotary kiln for 35 minutes to obtain a gelled material.

[0076] The heavy metal leaching (HJ 577-2010), dioxin content, and soluble chlorine content of the cementitious material meet the relevant requirements of the HJ 1134-2020 standard, and the cementitious performance meets the relevant requirements of the strength activity index in GB / T 1596, as shown in Table 9.

[0077] Table 9 Contaminant indexes of cementitious materials

[0078]

[0079] Further, the roadbed material is prepared by using the above-mentioned cementitious material, comprising the following steps:

[0080] According to the mass percentage, 70% of cementitious material, 10% of cement, 10% of lime and 10% of gypsum are mixed with 15% of water by solid mass for slurry mixing and injection molding to prepare semi-finished roadbed bricks. After curing for 1 day at about 40° C. and 70% humidity, the finished roadbed bricks are obtained.

[0081] The 7-day compressive strength of the finished roadbed brick is 16.4MPa, the 14-day compressive strength is 21.4MPa, and the 28-day compressive strength is 28.4MPa. The heavy metal leaching test was carried out in accordance with standard HJ 577, and the results met the relevant requirements of standard HJ 1134. The dioxin content and soluble chloride salts met the relevant requirements of standard HJ 1134, and the relevant test results are shown in Table 10.

[0082] Table 10 Product contamination index test results

[0083]

[0084] Comparative Example 1

[0085] The preparation method of the gelling material provided in this comparative example is basically the same as that of Example 1, except that the autoclave reaction temperature is 90°C.

[0086] The cementitious material obtained in this comparative example was subjected to heavy metal leaching results according to HJ 577, and the leaching concentrations of Cd and Pb were 0.2 mg / L and 1.9 mg / L respectively, exceeding the relevant requirements of HJ 1134.

[0087] Comparative Example 2

[0088] The preparation method of the gelling material provided in this comparative example is basically the same as that of Example 1, except that the high-temperature activation temperature is 300°C.

[0089] The dioxin content of the product obtained in this comparative example reaches 69 ng-TEQ / kg, exceeding the relevant requirements of HJ 1134.

[0090] Comparative Example 3

[0091] The preparation method of the cementitious material provided in this comparative example is basically the same as that of Example 2, except that: the fly ash in the mix ratio is 100%.

[0092] The cementitious material obtained in this comparative example was subjected to heavy metal leaching results according to HJ 577, and the leaching concentrations of Zn and Pb were 3.9 mg / L and 1.1 mg / L respectively, exceeding the relevant requirements of HJ 1134. At the same time, the strength activity index tested according to the GB / T 1596 method was 52%, which did not meet the relevant requirements of the standard.

[0093] Comparative Example 4

[0094] The preparation method of the gelling material provided in this comparative example is basically the same as that of Example 3, except that the autoclave temperature is 90°C.

[0095] The cementitious material obtained in this comparative example was subjected to heavy metal leaching results according to HJ 577, and the leaching concentrations of Zn, Pb, Cd and Ni were 3.1 mg / L, 1.8 mg / L, 0.2 mg / L and 1.1 mg / L respectively, which exceeded the relevant requirements of HJ 1134. At the same time, the strength activity index tested according to the GB / T 1596 method was 63%, which did not meet the relevant requirements of the standard.

Claims

1. A method for preparing a cementitious material by autoclaving and activating fly ash from garbage incineration, characterized in that: The following steps are involved: In terms of mass percentage, 50-80% fly ash, 18-50% auxiliary materials, 0-2% additives and water in an amount of 10%-30% of the total mass of the solid material are stirred, and pressed under a high pressure of 10-30 MPa for 4-5 minutes to form; The formed test block is placed in an autoclave and reacted at 150-250°C for 1-5 hours at a pressure of 0.5MPa-1.2MPa; The autoclaved test blocks were crushed, rinsed with water 1-3 times, and activated in a high-temperature kiln at 600-900°C for 20-60 minutes.

2. The method for preparing a cementitious material by autoclaving and activating waste incineration fly ash according to claim 1, characterized in that: The auxiliary material is a material containing silicon and aluminum components, and in the auxiliary material, the mass of silicon is greater than the mass of aluminum.

3. The method for preparing a cementitious material by autoclaving and activating waste incineration fly ash according to claim 2, characterized in that: The auxiliary material is fly ash.

4. The method for preparing a cementitious material by autoclaving and activating waste incineration fly ash according to claim 1, characterized in that: The additive is lime.

5. A method for preparing roadbed building materials, characterized in that: The following steps are involved: According to the mass percentage, 70-90% of the gelling material, 0-10% of the active stimulating material, 5-10% of the dehydrating agent, and 5-10% of the additive are mixed with 15-40% of the solid mass of water, stirred, rolled and mixed, and then slurry is adjusted and molded to prepare a semi-finished roadbed brick, or after being formed by high pressure of 5-20MPa, it is placed in an autoclave at 140-220°C and autoclaved for 2-6 hours to prepare a semi-finished autoclaved brick; the semi-finished roadbed brick or the semi-finished autoclaved brick is cured for 1-10 days under the conditions of 0-40°C and relative humidity of 70-100% to obtain a finished roadbed brick or a finished autoclaved brick.

6. The method for preparing roadbed building materials according to claim 5, characterized in that: The active excitation material is a silicon-containing or aluminum-containing material.

7. The method for preparing roadbed building materials according to claim 6, characterized in that: The active stimulating material is selected from fly ash, silica powder and cement.

8. The method for preparing roadbed building materials according to claim 5, characterized in that: The dehydrating agent is lime; the additive is gypsum.